Vitamin D Status in Children: A Hospital-Based Retrospective Study - Thapa, Sanjay Raj; Karki, Namrata; Ghimire, Amrit (Grande Medical Journal, 2025)
Background: Vitamin D deficiency is a common problem affecting both children and adult. It affects bone growth, derange immune function and have long term effect on health. This study examines serum Vitamin D level of pediatric patients and to know the magnitude of Vitamin D deficiency, insufficiency and sufficiency in children. Method: This retrospective study conducted at Grande International Hospital includes 1,403 children aged 0–14 years between January 2021 to December 2024. Data of serum Vitamin D levels were extracted from the hospital medical record. Children were subdivided by age (0–5 years, 6–10 years and 11–14 years) and Vitamin D levels were classified into deficiency (<12 ng/mL), insufficiency (12-20 ng/mL), and sufficiency (>20 ng/mL) groups. Result: 57.7% children were males and 42.3% children were females, with male having mean serum Vitamin D level of 27.79 ng/mL (SD 13.75) and female having 27.77 ng/mL (SD 16.41). Vitamin D deficiency was observed in 2.13%, insufficiency in 16.03%, and sufficiency in 81.84%. Deficiency and insufficiency are higher in older children, with deficiency rates of 1.05% (0-5 yrs), 2.49% (6- 10yrs), and 3.66% (11–14 yrs). Statistically significant sex differences were seen, with males at higher risk in ages 6–10 years and females at higher risk in ages 11–14 years. Conclusion: Majority of children have suboptimal Vitamin D level, with significant age and sex-related differences. Further study is needed for supplementation and screening programs.